Case report: A rare case of simultaneous necrotizing fasciitis of the breast and forearm - Xu, Ruofei; Fang, Tingting; Cai, Weikang (Frontiers in Medicine, 2024)
Necrotizing fasciitis is an aggressive bacterial infection that causes necrosis of the fascia and subcutaneous tissues with rapid progression and high mortality. Early stages often lead to misdiagnosis, resulting in improper treatment and severe implications. This case study presents a patient with diabetes mellitus combined with hepatitis B who rapidly developed necrotizing fasciitis of the left forearm and left breast after trauma and controlled the infection with early surgical treatment. It is worth noting that early surgical exploration is the gold standard for the diagnosis of necrotizing fasciitis and is the most effective means of reducing mortality and amputation rates in necrotizing fasciitis.